2006
DOI: 10.1111/j.1365-2753.2006.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

The clinical and cultural factors in classifying low back pain patients within Greece: a qualitative exploration of Greek health professionals

Abstract: An extensive Greek 'list' of clinical and cultural features was developed from the groups' analysis. Although similarities existed in most categories, there were several differences across the three focus groups which will be discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…This was a two-round modified Delphi survey. Initial data included in the first-round Delphi were generated by focus groups involving Greek PTs and doctors and is described elsewhere [31]. Ethical approval was obtained from the Ethical Committees of Technological Educational Institute of Lamia, Greece and University of Manchester, UK.…”
Section: Methodsmentioning
confidence: 99%
“…This was a two-round modified Delphi survey. Initial data included in the first-round Delphi were generated by focus groups involving Greek PTs and doctors and is described elsewhere [31]. Ethical approval was obtained from the Ethical Committees of Technological Educational Institute of Lamia, Greece and University of Manchester, UK.…”
Section: Methodsmentioning
confidence: 99%
“…In all except two European studies [57,74] the profession involved in developing the classification systems was the medical profession; which could indicate the dominance of the 'medical' model throughout Europe [9]. Also most classification systems were diagnostic [5,[19][20]74], and psychosocial questionnaires were one of the most commonly used discriminatory criteria for subgroup classification.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Greek physiotherapists are only covered by health insurances for treating their patients and not for assessing them, or for deciding on treatment; these procedures are legally considered as medical ones [9]. Thus, 'cultural' issues have an impact on how LBP is managed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first study accompanying this publication (10) reports the intertester reliability of a suggested discriminatory list, derived from the consensus of a large number of health professionals (11,12). This reliability study enabled the identification of items that presented with a kappa value of 0.41 or more, corresponding to moderate and substantial/excellent agreement (13).…”
Section: Testing Proceduresmentioning
confidence: 99%